Ett socialt spel ⁠— inte en flykt från den verkliga världen - Norlén, Anne-Christine (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
In this article I discuss interaction on the Internet as a social game, not an escape from reality. A lot of people argue that the experience of confirmation is as real on the net as in face-to-face interaction. I argue that there is an underlying moral issue to the discussions on the use of Internet, as well as those of online games and online interaction. In the media the machine and the technology are often blamed for the online flirting, when in fact they are human behavior and human actions.